A Block Design for Introductory Functional Programming in Haskell - Poole, Matthew (2019 IEEE Blocks and Beyond Workshop (B&B), 2019)
The following topics are dealt with: computer science education; computer aided instruction; programming environments; educational courses; programming; teaching; object-oriented programming; programming languages; handicapped aids; serious games (computing).